(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
Even today, bilingual teaching in Serbia is seen as a pedagogical innovation, although it has been carried out continuously for 14 years. From the standpoint of the analysis of language education policies as public policies, this fact raises several questions, one of which is the role of various actors in the process of its introduction, implementation and evaluation. By recording the most important domestic experiences that preceded the introduction of bilingual teaching in 2004 in two Belgrade educational institutions and analyzing certain aspects of these experiences, this paper seeks to answer the question of the performance of different actors in developing this teaching model, but also to point out problems which appear as a constant, that is, which have not been effectively resolved so far, put the view of the past in the function of the future development of bilingual teaching.